Uprootedness and the protection of migrants in the International Law of Human Rights - Trindade,Antônio Augusto Cançado (2008)
The article attempt to demonstrate the evolution of international law in connected to the subject of the forced immigrants'. The author supported by several texts, cases and resolutions of the regional level, through interamerican court and European court, and the global level, through the international court. It's shown the evolution that occurred in international law in millennium turn over, which recognize the immigrants' rights. However, it's stressed the necessity of the development of those laws connected to the theme e the recognition, from the States; the importance of law's that effort to ensure the respect to human rights relative to the immigrants and their families.